Prospective Long-Term Evaluation of Meniscal Allograft Transplantation Procedure: A Minimum of 7-Year Follow-Up - Saltzman, Bryan M.; Bajaj, Sarvottam; Salata, Michael; Daley, Erika L.; Strauss, Eric; Verma, Nikhil; Cole, Brian J. (The Journal of Knee Surgery, 2012)
This study reports the long-term effectiveness of meniscal allograft transplantation performed by a single senior operating surgeon. In this study 22 meniscus transplantations in 22 patients were evaluated at a minimum of 7-year follow-up (mean 8.5 ± 1.3 years) using standardized scoring scales. Subgroup analysis was performed to stratify outcomes based on medial (59.1%) versus lateral (40.9%) meniscus transplantation, and transplantations performed in isolation (36.4%) versus those performed concomitantly (63.6%). Patients reported significant improvement in all scoring scales (p < 0.05). Average satisfaction was 8.8 out of 10. All the patients were completely or mostly satisfied with the results of their surgery. Overall subjective knee condition improved from 3.5 to 6.9 (p < 0.05). Patients undergoing medial compartment repair and combined transplantations reported greater improvement from baseline to follow-up than did their counterparts. An overall success rate of 88% was found for all patients at the final follow-up. Based on this data, meniscal allograft transplantation is a viable treatment option for meniscal-deficient patients in reducing pain, increasing range of motion, and improving patient function and satisfaction at a minimum of 7 years postsurgery.
Keywords: meniscus; meniscus transplant; meniscectomy; allograft; long-term efficacy